Modular and Reconfigurable Wireless E‐Tattoos for Personalized Sensing. Issue 8 (14th May 2019) - Jeong, Hyoyoung; Wang, Liu; Ha, Taewoo; Mitbander, Ruchika; Yang, Xiangxing; Dai, Zhaohe; Qiao, Shutao; Shen, Linxiao; Sun, Nan; Lu, Nanshu
Abstract: In the past few years, ultrathin and ultrasoft epidermal electronics (a.k.a. e‐tattoos) emerged as the next‐generation wearables for telemedicine, mobile health, performance tracking, human‐machine interface (HMI), and so on. However, it is not possible to build an all‐purpose e‐tattoo that can accommodate such a wide range of applications. Thus, the design, fabrication, and validation of modular and reconfigurable wireless e‐tattoos for personalized sensing are reported. Such e‐tattoos feature a multilayer stack of stretchable layers of distinct functionalities—a near field communication (NFC) layer capable of wireless power harvesting and data transmission, a functional circuit layer, and a passive electrode/sensor layer. These layers can be disassembled and swapped out multiple times to form different e‐tattoos of different sensing capabilities. Such modular and wireless e‐tattoos can be rapid‐prototyped via a dry, digital, and cost‐effective fabrication process—the "cut‐solder‐paste" process. They have been successfully applied to wirelessly measure a variety of biometrics. Abstract : Moving from traditional healthcare methods of monitoring biometrics to an individualized wearable modality promises to reduce healthcare expenses and to present better value to the end‐user. Here, the design, fabrication, and validation of modular and reconfigurable wireless e‐tattoos for personalized healthcare monitoring are reported. Such e‐tattoos have been successfully applied to wirelessly measure a variety of biometrics on the skin.